Pemanfaatan Kotoran Hewan dan Limbah Pertanian sebagai Kompos dalam Usaha Peningkatan Produksi Sayuran di Desa Ake Ara Jailolo Selatan Halmahera Barat - Sofyan, Adnan; Rachman, Idris Abd; Hartono, Gunawan; Hasan, Asrul Dedy Ali (Program Studi Kehutanan, Universitas Khairun, 2023)
Abstract Farming communities have not utilized agricultural waste and animal waste as compost optimally in overcoming the scarcity of fertilizer in farming communities. Composting is an alternative way of creating natural fertilizer made by farmers themselves, thus responding to the scarcity of fertilizer which in turn improves the health quality of the soil, produces healthy plant products, and increases farmers' income. The solutions offered in the program include the presentation of compost making materials, how to apply them to plants, assistance in plant cultivation business activities, post-harvest handling so that plant products can be maintained in a healthy manner. It is hoped that the farmers as partners who are accompanied can produce organic compost fertilizer which can increase crop production and increase their income. The aim of this program is to improve farmers' skills in utilizing plant litter, agricultural waste, animal waste to make compost fertilizer, which can then be sold on the market or used by farmers themselves to improve their vegetable cultivation business. Stages of activities include socialization, presentation of counseling material, creation of compost demonstration plots and plant cultivation demonstration plots with stages of land preparation, seeding, making plots, planting, fertilizing, watering, maintaining plants until harvest and marketing the results of cultivated plants. Keywords: Training, Compost, Farmers, Production, Chaisim